Association of individual and community factors with C-reactive protein and 25-hydroxyvitamin D: Evidence from the National Health and Nutrition Examination Survey (NHANES). (December 2016) - Chai, Weiwen; Fan, Jessie X.; Wen, Ming
Abstract: Many individual and community/neighborhood factors may contribute to inflammation and vitamin D deficiency leading to the development of chronic diseases. This study examined the associations of serum C-reactive protein (CRP) and 25-hydroxyvitamin D [25(OH)D] levels with individual and community/neighborhood (tract-level or county-level) factors using a nationally representative sample from 2001–2006 National Health and Nutrition Examination Survey (NHANES). Data from the 2001–2006 waves of the continuous NHANES was merged with the 2000 census and other neighborhood data sources constructed using geographic information system. Associations between multilevel factors and biomarker levels were assessed using multilevel random-intercept regression models. 6643 participants aged 19–65 (3402 men and 3241 women) were included in the analysis. Family income-to-needs ratio was inversely associated with CRP (P=0.002) and positively associated with 25(OH)D levels (P=0.0003). County crime rates were positively associated with CRP (P=0.007) and inversely associated with 25(OH)D levels (P=0.0002). The associations with income-to-needs ratio were significant in men [CRP, P=0.005; 25(OH)D, P=0.005] but not in women. For county crime rates, the association was only significant in women for CRP (P=0.004) and was significant in both men (P=0.01) and women (P=0.001) for 25(OH)D. Additionally, overall CRP was positively associated with age (P<0.0001), female sex (P<0.0001), Hispanic race/ethnicity (P=0.0001), current smokers (P<0.0001), body mass index (BMI, P<0.0001), and participants who were US-born (P=0.02). Non-Hispanic black (P<0.0001) and Hispanic race/ethnicity (P<0.0001), current smoker (P=0.047), and higher BMI (P<0.0001) were associated with lower serum 25(OH)D levels. No significant associations were observed between other community/neighborhood variables and serum CRP and 25(OH)D levels. The current results suggest that family income-to-needs ratio and county crime rate may be important contributors to chronic inflammation and vitamin D status. Highlights: Significantly inverse association of CRP with family income-to-needs ratio. Significantly positive association of CRP with county crime rates. Significantly positive association of 25-hydroxyvitamin D with family income-to-needs ratio. Significantly inverse association of 25-hydroxyvitamin D with county crime rates. Family income-to-needs ratio and county crime rate may be important factors contributing to chronic inflammation and vitamin deficiency.